Drought Vulnerability and Child Mobility in Rural Senegal. Issue 3 (1st September 2020) - Kielland, Anne; Kebede, Tewodros Aragie
Abstract: Are children of rural households vulnerable to climate-related shocks more likely to live away from the parental household? What is the relationship between household drought shock vulnerability and child mobility, independent of factors such as poverty and traditional social practices? This article applies propensity score matching on household data from rural Senegal to address these questions. The results indicate a statistical association between households being drought-shocked and having at least one child living away of between 14 and 18 per cent, and of 13–19 per cent to having young boys who study the Quran away from home as so-called talibés.